Monotheism, intolerance, and the path to pluralistic politics - Haw, Christopher A. (University of Cambridge ESOL Examinations, 2021)
Explores the dangers and benefits of monotheistic intolerance, interacting with scholars of monotheism, evolutionary theory, and agonistic pluralism.